Interplay Between the Phenotype and Genotype, and Efflux Pumps in Drug-Resistant Strains of Riemerella anatipestifer - Chen, Qiwei; Gong, Xiaowei; Zheng, Fuying; Ji, Guo; Li, Shengdou; Stipkovits, Laszlo; Szathmary, Susan; Liu, Yongsheng (Frontiers in Microbiology, 2018)
The number of multidrug-resistant strains of Riemerella anatipestifer continues to increase and new strategies for the treatment of associated infections are necessary. Recently, numerous studies have shown that efflux pumps (EPs) play key roles as universal bacterial mechanisms that contribute to antibiotic resistance. In addition, studies have shown that the effects of antibiotics subjected to efflux can be reinforced by the combined use of efflux pump inhibitors (EPIs). Unfortunately, the role of the efflux system in R. anatipestifer remains barely understood. In this study, we evaluated the role of EPs and resistance genes in the resistance of clinical strains of R. anatipestifer to antibiotics. A set of 10 R. anatipestifer strains were characterized by drug resistance, associated resistance genes, and antibiotic profiles in the presence and absence of EPIs. Efflux activity was studied on a real-time basis through a fluorometric method. Quantification of the mRNA transcriptional levels of efflux pump genes (EPGs) was determined by RT-qPCR. Several approaches (detection of resistance genes, drug susceptibility testing, and growth kinetics analysis) were used to assessed the correlation between the effect of the EPIs and resistance levels. Analysis of the R. anatipestifer growth inhibition tests showed that antibiotic activity was enhanced by the synergy of EPIs. Among the various resistance genes conferring antibiotic resistance, different minimum inhibitory concentrations (MICs) were observed. The different levels of resistance observed could have been reduced by EPIs. Real-time fluorometry showed that all R. anatipestifer strains presented inherent efflux activity, conferring varying levels of inhibition in the presence of EPIs. Moreover, 15 EPGs were overexpressed in the presence of antibiotics. The addition of EPIs to antibiotics led to downregulation in the expression of some EPGs, and a simultaneous increase in drug resistance and sensitivity. These results demonstrated the contribution of these EPs in the resistant phenotype of the R. anatipestifer clinical strains under investigation, independently of the resistant genotype of the respective strains. Intrinsic efflux activity was possibly linked to the evolution of resistance in multidrug-resistant isolates of R. anatipestifer. Furthermore, the inhibition of EPs by EPIs could enhance the clinical effects of antibiotics.